DETERMINASI PERTUMBUHAN EKONOMI DI ASEAN - Taufiq Rahman; Jakaria , (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
This study aims to determine the relationship between Foreign Direct Invesment, Gross Fixed Capital Formation, Trade Openness to economic growth in nine ASEAN countries, and to compare the factors that determinae the movement and economic growth ini nine countries ASEAN. The variables used invlude foreign direct investment, gross fixed capital formation, trade openness and Growth of Gross Domestic Product of each country. The method used in this thesis is the regression method Panel . Results of the study showed an overall variable Foreign Direct Investment and Gross Fixed Capital Formation had significant results . If seen from the results of the model for pernegara Foreign Direct Investment have the significant results in the state of Singapore . Gross Fixed Capital Formation have the significant results in the state of Singapore, Thailand, Philippines and Cambodia. To have the variable Trade Openness significant results at the state of Indonesia, Malaysia, Thailand, Philippines, and Cambodia.